Panaghoy sa suba The call of the river - Montano, Cesar; Plaza, Victoria; Vertido, Cris.; CM Films, Inc. (Manila CM Films, Inc., 2004)
During the Japanese Occupation in the Philippines, in the island province of Bohol, located in Central Visayas, a banca-operator-turned-guerilla named Duroy (Cesar Montano) fell in love with Iset (Juliana Palermo), a lovely lass from the same village where the people's main thoroughfare is a river. John Smith (Philip Anthony), an American stingy landowner was captured by Iset's beauty as well as Duroy's brother Ibo (Reiven Bulado). Since Ohkohara (Jackie Woo), a handsome Japanese officer takes over in the village; he also falls in love with Iset. During the Japanese Era, Duroy joins a band of guerillas and later becomes their leader mainly because of his talent in creating innovative methods of fighting the enemy. Iset, on the other hand is appalled at the brutality of the Japanese and her father's collaboration with them. She makes a bold move against her parents and what they stand for by joining the guerillas. After a series of sorties, Duroy leads a final assault over the Japanese and succeeded. It boosted love self esteem as an underachiever and illiterate person. What appears to be a battle won in love and in war takes a strange twist in the end with the return of the American suitor. Duroy, after getting rid of the ghost of his troubled and deprived past, decides for everyone else: He answers the insistent call of the river.
Summary taken from cover.
Associate producer, Sunshine Cruz-Montano and RD Alba ; Assistant director, Glenn R. Parian ; Executive producers, Yoshihuki Ohira, Mary Ann Dy, Anthony Go, Ismael Reyes, Romeo Chong, Robert Yu, Victoriano Plaza and Cesar Montano.
Cesar Montano, Juliana Palermo, Jacky Woo, Caridad Sanchez, Ronnie Lazaro, Joel Torre, Daria Ramirez, Rommel Montano, Phil Anthony, Suzette Ranillo & Rebecca Lusterio ; introducing, Rowald Montano and Reiven Bulado.
VCD
In Cebuano with English subtitles.
Winner for Special Grand Prix of the Jury (Festival International Du Film Independent-Belgium); 6th Special Jury Prize (3rd Bali International Film Festival 2005-Indonesia); Best Cinematography (2005 FAP Awards, 2005 Gawad Urian & 2004 MMFF); Best Musical Scoring (2005 FAP Awards, 2005 Gawad Urian & 2004 MMFF); Best Sound (2005 Gawad Urian); Best Screenplay (2005 FAP Awards, 2005 Gawad Urian); Best Supporting Actress (2004 MMFF); 2nd Best Film for Gatpuno Antonio J. Villegas Cultural Award (2004 MMFF); Best Actor (2005 Gawad Urian); Best Director (2005 Brussels International Film Festival).
Keywords: Feature films; Fiction films